2018
DOI: 10.1177/1479164118785314
|View full text |Cite
|
Sign up to set email alerts
|

Skin autofluorescence is associated with high-sensitive cardiac troponin T, a circulating cardiac biomarker, in Japanese patients with diabetes: A cross-sectional study

Abstract: The study aims to evaluate the relationship between skin autofluorescence, a marker of advanced glycated end-products accumulation in tissue, and high-sensitive cardiac troponin T, a cardiovascular biomarker, in Japanese subjects with diabetes. A total of 145 subjects with diabetes and 32 nondiabetic subjects as control attending the outpatient clinic were examined. Skin autofluorescence was measured using the AGE Reader™. Univariate and multivariate regression analyses were used to identify the factors associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Moreover, they also clarified that the AGEs found at the volar side of the lower arm appear to reflect the level of AGEs/RAGEs in the cardiomyocytes. In fact, there are several clinical studies that show significant relationships between skin AF and biomarkers of myocardial injury [13,34]. Although markers of myocardial injury were not evaluated in the present study, previous studies have shown that AGEs/RAGEs are believed to play important roles in the progression of myocardial injury; consequently, HFpEF patients with high skin AF may be particularly prone to becoming hospitalized due to HF.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, they also clarified that the AGEs found at the volar side of the lower arm appear to reflect the level of AGEs/RAGEs in the cardiomyocytes. In fact, there are several clinical studies that show significant relationships between skin AF and biomarkers of myocardial injury [13,34]. Although markers of myocardial injury were not evaluated in the present study, previous studies have shown that AGEs/RAGEs are believed to play important roles in the progression of myocardial injury; consequently, HFpEF patients with high skin AF may be particularly prone to becoming hospitalized due to HF.…”
Section: Discussionmentioning
confidence: 81%
“…Among the methods used to evaluate AGEs, skin autofluorescence (AF) is known to be a simple and reliable marker in vivo, and recent clinical studies have indicated that skin AF levels are significantly associated with cardiovascular disease incidence and risk factors [8][9][10]. Moreover, several studies have found an association between skin AF and the pathogenesis of HF [11][12][13]. However, data on the usefulness of skin AF as a predictor of CHF are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, skin autofluorescence, a biomarker of advanced glycation end-products, was associated with both serum hs-cTnT concentrations and sarcopenia in diabetic patients [ 38 , 39 ]. In patients with skeletal muscle disease, transcriptions of genes coding for cTnT were up-regulated in skeletal muscles but that of cTnI was at normal level [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hitsumoto et al [54] report that SAF can be considered novel CV risk factors, alongside in vivo oxidative stress, and high arterial reflection, because they are closely associated with high concentrations of blood hs-cTnT in patients with T2DM. Moreover, in a study by Yoshioka [55], SAF can predict CV risk in patients with T2DM, being correlated with elevated hs-cTnT and NT-proBNP. Another CV risk identified by Hitsumoto [56] is the prediction of the risk of first HF hospitalization in patients with HFpEF.…”
Section: Biologic Biomarkers Associationsmentioning
confidence: 96%